2021
DOI: 10.31757/euer.422
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Turkish Cultural Adaptation of International Students Living in Turkey

Abstract: In this study, the cultural adaptations of international students studying in Samsun in acculturation processes were examined. The cultural problems that international students inevitably face affect their adaptation to the countries they host. To investigate the effects of the international students' some variables on the cultural adaptation in the context of Turkey constitutes the main objective of this study. In the study, it was examined whether the cultural adaptation levels of international students var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…Results from the focus group discussions showed that international students face challenges in their everyday life, dormitory life, campus life, social life and academic life. (Gebru et al, 2020) Eynullayeva et al (2021 examined whether the cultural adaptation levels of international students vary according to gender, place of residence, academic achievement level, education level, faculty they attend, and their age.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the focus group discussions showed that international students face challenges in their everyday life, dormitory life, campus life, social life and academic life. (Gebru et al, 2020) Eynullayeva et al (2021 examined whether the cultural adaptation levels of international students vary according to gender, place of residence, academic achievement level, education level, faculty they attend, and their age.…”
Section: Discussionmentioning
confidence: 99%